Regional Economic Outlook, April 2016, Asia and Pacific : Building on Asia's Strengths during Turbulent Times - Salgado, Ranil (Washington, D.C. : International Monetary Fund, 2016)
Although Asia remains a growth leader in the global economy, growth is expected to ease slightly to 5.5 percent during 2016, with countries affected to varying degrees by a still weak global recovery, slowing global trade, and the short-term impact of China's growth transition. Structural reforms are needed if Asia is to maintain its position in the global economy, including reforms aimed at enhancing productive capacity. Needed reforms range from state-owned enterprise and financial sector reform in China to labor and product market reforms in Japan and reforms to remove supply bottlenecks in India, ASEAN, frontier economies, and small states.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet